Analysis of Conflict Found in the Novel The Girl Who Drank the Moon by Kelly Barnhill - Zahra Alya Hayahanifah; Imas Istiani (University of Surakarta, 2025)
Conflict can occur anywhere and anytime, caused by internal or external factors. Thus, this study was done to help inform the concept of conflict in both fiction and real life. This study examines the conflicts in the novel “The Girl Who Drank the Moon” by Kelly Barnhill through the lens of William Kenney's literary conflict theory framework. The purpose of this study is to identify and understand the conflicts faced by the characters in the novel. Then, the method used was for the researcher to read the novel intensively, observe, and take notes to identify conflicts in the novel. The analysis is based on primary data, presented as scenes and dialogue in the novel. To organize qualitative research, the researcher applied the Miles and Huberman framework, which consists of three main steps: data reduction, data presentation, and concluding with verification. The research findings revealed that various conflicts occur in this novel, both internally and externally. The findings can be used to deepen the understanding of the conflicts in the novel or real life and to fill the gap in research related to this novel.